Clinical features and management of Trypanosoma evansi infection in buffaloes - SINGH, BHAVJOT; SINGLA, L D; KAUR, PARAMJIT (The Indian Journal of Animal Sciences, 2024)
Trypanosoma evansi is a haemoprotozoan that causes a severe disease called as Surra in domestic and wild mammals. The disease is endemic in India and the clinical symptoms of disease can vary depending on the host species but generally include fever, anaemia, weight loss, weakness, neurological signs and decreased production capacity. In this study, the clinical observations of the six buffaloes that showed signs of emaciation, corneal opacity, oedema, and circling behaviour was done. All the suspected animals (n=06) were tested for Trypanosoma by a combination of methods to detect the presence of the parasite by microscopy, Card Agglutination Test for Trypanosomiasis (CATT) and Polymerase Chain Reaction (PCR). Only three animals were diagnosed positive by microscopy. All buffaloes were found positive for Trypanosoma infection by CATT and PCR assay. The haematological and biochemical test indicated significant fall in total haemoglobin (Hb), total erythrocyte count (TEC), packed cell volume (PCV), glucose, total protein, and albumin levels. Additionally, there were appreciable elevations in blood urea nitrogen (BUN), creatinine, gamma-glutamyl transferase (GGT), and total bilirubin levels, indicating liver and renal malfunction. One animal succumbed to infection and had acute peritoneal oedema in postmortem observations. The report underlines the significant clinical and biochemical changes linked to evansi infection in buffaloes. The study also highlights the need of early detection and treatment in reducing the negative effects of trypanosomiasis on animal health and production.